2018
DOI: 10.1093/nar/gky921
|View full text |Cite
|
Sign up to set email alerts
|

Modulation ofMKNK2alternative splicing by splice-switching oligonucleotides as a novel approach for glioblastoma treatment

Abstract: The gene encoding the kinase Mnk2 (MKNK2) is alternatively spliced to produce two isoforms—Mnk2a and Mnk2b. We previously showed that Mnk2a is downregulated in several types of cancer and acts as a tumor suppressor by activation of the p38–MAPK stress pathway, inducing apoptosis. Moreover, Mnk2a overexpression suppressed Ras-induced transformation in culture and in vivo. In contrast, the Mnk2b isoform acts as a pro-oncogenic factor. In this study, we designed modified-RNA antisense oligonucleotides and screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 36 publications
1
42
0
1
Order By: Relevance
“…Alternative selection of the two last exons in the MNK2 kinase gene (MKNK2) yields either the MNK2a variant, which displays tumor suppressor activity, or the pro-oncogenic MNK2b variant. In vivo delivery of an SSO that efficiently promotes splicing of MNK2a inhibited GBM growth and sensitized GBM cells to chemotherapeutic agents [129]. Comparable anti-cancer results were obtained by employing the same strategy to promote splicing of a truncated inactive telomerase subunit (hTERT).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Alternative selection of the two last exons in the MNK2 kinase gene (MKNK2) yields either the MNK2a variant, which displays tumor suppressor activity, or the pro-oncogenic MNK2b variant. In vivo delivery of an SSO that efficiently promotes splicing of MNK2a inhibited GBM growth and sensitized GBM cells to chemotherapeutic agents [129]. Comparable anti-cancer results were obtained by employing the same strategy to promote splicing of a truncated inactive telomerase subunit (hTERT).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…For example, Barbagallo et al found that circSMARCA5 negatively regulated splicing of VEGFA through splicing factor SRSF1, which exerted antiangiogenic function . Mogilevsky et al discovered that the manipulation of MKNK2 AS significantly suppressed the oncogenic properties of GBM cells and resensitized the cells to chemotherapy, which suggested a novel treatment strategy for clinical practice . However, the literature primarily focuses on one AS and is lacking an exhaustive overview of all splicing events.…”
Section: Introductionmentioning
confidence: 99%
“…21 Mogilevsky et al discovered that the manipulation of MKNK2 AS significantly suppressed the oncogenic properties of GBM cells and resensitized the cells to chemotherapy, which suggested a novel treatment strategy for clinical practice. 22 However, the literature primarily focuses on one AS and is lacking an exhaustive overview of all splicing events. In Sadeque's study, the prognostic value of alternative exon usage, a broad category of AS, was comprehensively investigated in GBM patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, oligonucleotides are well suited to modulate mRNA splicing since they bind with high selectivity directly to the disease-causing element. Consequently, there is considerable excitement for a wave of SSOs that are currently in pre-clinical and clinical development (32,(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%